THE EFFECT OF “ANTICIPATION GUIDE STRATEGY” AND STUDENTS’ READING INTEREST ON STUDENTS’ READING COMPREHENSION AT GRADE XII OF SMKN 1 PARIAMAN. - Darvius Antoni (English Language Teaching and Research, 2017)
This research was conducted to find out the effect of Anticipation Guide strategy and students’ reading interest on students’ reading comprehension of procedure Text. The design of this research was quasi experimental with 2x2 factorial design. The population of this research was the twelfth grade of SMKN 1 Pariaman, 2014/2015 academic year. Reading Comprehension test and reading interest questionnaire were used as research instruments. Then, the data were analyzed using t-test formula and Two Ways ANOVA. The result of this research shows that (1) students who were taught by using Anticipation Guide Strategy had better reading comprehension of procedure text than those who were taught by Small Group Discussion. It was proven by the result of the t-test which showed that tobserved was bigger than ttable, (2) students who had high reading interest taught by Anticipation Guide Strategy had better reading comprehension of procedure text than those who were taught by Small Group Discussion,(3) students who had low reading interest taught by Anticipation Guide Strategy had better reading comprehension of procedure text than those who were taught by Small Group Discussion, and (4) there was no interaction between both strategies and students reading interest toward students’ reading comprehension where F-observed was 0,53 which less than F-table 4,15. As conclusion, Anticipation Guide Strategy had a significant result on students’ reading comprehension than Small-Group Discussion and there was no interaction between teaching strategies and reading interest on students’ reading comprehension. Key words/phrases: Anticipation Guide, Reading Interest, Reading Comprehension